A Quiet Mind : Buddhist Ways to Calm the Noise in your Head - Matsumoto, Shoukei (London : Welbeck, 2020)
Drawing on the practices, beliefs and teachings of Buddhism, this book reveals the benefits of turning your consciousness inwards and with a new awareness teaches you how to quieten your mind and find calm in a chaotic world.
Formerly CIP.
Keywords: Self-actualization (Psychology) -- Religious aspects -- Buddhism; Peace of mind -- Religious aspects -- Buddhism; Mindfulness (Psychology)